Maintenance of the 2 microns circle plasmid in populations of Saccharomyces cerevisiae. - Futcher, A B (1983)
The 2 microns circle plasmid is maintained at high frequencies in populations of yeast cells. To find out how the plasmid is maintained, three forces were measured: the selective advantage or disadvantage conferred by 2 microns circles, the rate of generation of [Cir0] cells, and the rate of illegitimate transfer of 2 microns circles from cell to cell. It was found that under the conditions used, 2 microns circles confer a selective disadvantage of about 1%, that [Cir0] cells are generated at the rate of 7.6 x 10(-5) per [Cir+] cell per generation, and that illegitimate transfer of 2 microns circles occurs at a rate less than 10(-7) per recipient cell per generation. The most likely explanation of 2 microns circle maintenance is that the plasmid is sexually transmitted at such a rate that it spreads through populations despite selection against it.